Compositional and structural design of thermoplastic polyurethane/carbon based single and multi-layer composite sheets for high-performance X-band microwave absorbing applications. (10th October 2019) - Kasgoz, Alper; Korkmaz, Mehmet; Durmus, Ali
Abstract: In this study, morphological features, dielectric properties, and microwave absorbing performances of thermoplastic polyurethane composite sheets prepared with solution mixing method by using different amounts and types of carbon fillers, carbon black (CB), graphite (G), carbon nanofiber (CNF), and multiwalled carbon nanotube (MWCNT) were investigated, in detail. Microstructural properties and microwave absorbing characteristics of composites were analyzed with scanning electron microscope and vector network analyzer by transmission line method, respectively. Reflection loss (RL) analyses of composites showed that CNF and CNT were more efficient than CB and G for improving the electromagnetic wave absorbing performances of sheets at low filler contents. It was found that the broadest effective absorption area (EAA) (10.03–12.96 GHz) was obtained with the sample having 3 phr of CNF. However, single layer TPU/carbon composite sheets were not effective "RADAR stealth" materials because their RL values were higher than −10 dB at X-band. Thus, multilayer (two, three, and four-layer) composite structures were designed to obtain higher microwave absorption performance within this frequency range via genetic algorithm approach. Multilayer design and modeling works showed that a four-layer composite with a total thickness of 4.8 mm yielded excellent microwave absorbing performance and broad EAA, 6.98–13.415 GHz, at X-band. Graphical abstract: Image 10060 Highlights: TPU composite sheets filled with different carbon fillers (CB, CNT, CNF, and EG) were prepared. Electromagnetic properties of composites were characterized within 2–14 GHz for radar absorbing applications. Effective absorption area (EAA) and Reflection Loss ( RL ) values were computed as a function of compositional variations. Multi-layered composites were designed to improve EAA and RL values via genetic algorithm approach. Four-layer composite (4.8 mm) exhibited excellent microwave absorbing performance (EAA of 6.43 GHz and RL of 33.9 dB).